Las excusas de los jueces, en las garantías jurisdiccionales de derechos y su incidencia en los principios constitucionales de celeridad y la debida diligencia. - Maroto Acosta, Iván Andrés (2023)
The investigation is born from the excuses of the judges, in the jurisdictional guarantees of rights and its incidence in the constitutional principles of speed and due diligence since there are so many professionals who have problems in the adequate resolutions of their cases, as a general objective it is proposed determine the incidence of the excuses of the judges in the Constitutional Guarantees of Rights on the principles of celerity determining the legality of the competence of the judge, when the excuse is denied in a judicial action and its due diligence. As a methodology, the mixed method is applied, which refers to obtaining quantitative and qualitative data, with bibliographic, field, descriptive and explanatory research, using the survey and case analysis as a technique and instrument where it can be evidenced that Due to the excuses of the judges within the Jurisdictional Guarantees, an adequate resolution is not allowed since the provisions of Article 76 numeral 7 literal k of the Constitution of Ecuador are not complied with, which should be respected and applied so that there is no delay in the cases. In the same way, the reasons for excuse and recusal have been examined, as well as the definitions proposed by various thinkers, jurists and academics, to make a deep analysis of the matter investigated, and thus understand each of the points of view of both the judges and the judges as well as the lawyers presenting their respective case.